Determinantes, factores contextuales y personales de la Intención Emprendedora de los estudiantes de la Universidad de Murcia. 2015 (EDITUM. Ediciones de la Universidad de Murcia, 2025)
Publication that analyzes the entrepreneurial intention of the students of the University of Murcia. The report responds to the request of the Social Council of the University of Murcia that aims to publicize the current predisposition of the students of the University of Murcia to generate business ideas and undertake.The report has been made from the participation of 2,280 students enrolled in graduate and 413 postgraduate studies. The entrepreneurial intention has been measured from a planned behavior model that has been validated in scientific literature for its ability to predict entrepreneurial activity. The entrepreneurial intention of the students is analyzed deepening the explanatory factors that lead to the decision to undertake: entrepreneurial attitude, social pressure and perceived control. In addition, a broad analysis of the determinants of the entrepreneurial intention, inconveniences and professional trajectories is included based on the main contextual factors: gender, age access to the university, studies that currently attend at the university, distinguishing by branches of knowledge, Academic level and degree degrees, work experience, parents' studies, and socioeconomic group of families. Based on the results of this study, measures that favor attitude and entrepreneurial and business training can be taken at all levels of university education in order to favor the entrepreneurial activity of the students of the University of Murcia.